Trade And Human Capital Accumulation : Evidence From U.S. Immigrants - Dömeland, Dörte, 1971- 1971- (The World Bank, 2007)
This study provides empirical evidence that trade increases on-the-job human capital accumulation by estimating the effect of home country openness on estimated returns to home country experience of U.S. immigrants. The positive effect of trade on on-the-job human capital accumulation remains significant when controlling for GDP, educational attainment, and institutional quality. It is not the result of self-selection, heterogeneity in returns to experience, English-speaking origin, or cultural background. The effect persists when restricting the sample to non-OECD countries, thereby resolving the theoretical ambiguity of whether trade increases or decreases learning-by-doing. The role of trade in generating economic growth is therefore likely to be more important than generally considered